2017
DOI: 10.3390/f8030084
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Inter-Tree Competition and Its Role in Shaping the Community Structure of a Natural Mongolian Scots Pine (Pinus sylvestris var. mongolica) Forest

Abstract: Abstract:Inter-tree competition is considered one of the most important ecological processes of forest development. However, its importance in structuring the spatial patterns of plant communities remains controversial. We collected observational data from two plots in a natural Mongolian Scots pine forest to study the contribution of competition to tree growth, mortality, and size inequality. We used the nearest neighbour method to determine the presence of competition, and unmarked and marked spatial point p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…9. The spatial pattern of natural regeneration on permanent research plots 1-6 expressed by Lfunction in 2016; the black line represents the L-function for real distances of recruits; the bold grey line represents the mean course for random spatial distribution and the two thinner central curves represent 95% interval of reliability; when the black line of recruits distribution on the plots is under (below) this interval, it indicates a tendency of recruits toward aggregation (regular) distribution ecosystems are rightfully receiving more and more attention (Popa et al, 2017;Wang et al, 2017). The structure and growth of pine stands in the Czech Republic were dealt with by Bílek et al (2016); or Sharma et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…9. The spatial pattern of natural regeneration on permanent research plots 1-6 expressed by Lfunction in 2016; the black line represents the L-function for real distances of recruits; the bold grey line represents the mean course for random spatial distribution and the two thinner central curves represent 95% interval of reliability; when the black line of recruits distribution on the plots is under (below) this interval, it indicates a tendency of recruits toward aggregation (regular) distribution ecosystems are rightfully receiving more and more attention (Popa et al, 2017;Wang et al, 2017). The structure and growth of pine stands in the Czech Republic were dealt with by Bílek et al (2016); or Sharma et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the crown diameter of Mongolian pine increased with both age and stand density [65]. As crowns may overlap, competition is a crucial factor that affects Mongolian pine growth [66]; thus, trees growing in a dense forest may undergo decline more readily. Trees in low-density stands were reported to show greater R t and R c , indicating that trees growing at lower densities were less vulnerable to the harmful effects of drought [3] and high-density stands were more sensitive to climatic fluctuations (particularly precipitation).…”
Section: Vulnerability To Droughtmentioning
confidence: 98%
“…In order to explore spatial correlation structure in terms of quantitative tree mark of tree, tree size (height) was used as a "mark" in a mark correlation function (MCF) and mark variograms function (MVF) [37][38][39][40][41][42]. The MCF analysis is similar to the pair-correlation function g(r), but it allowed us to detect density-dependent size correlation caused by competition in nearby tree individuals [40,41].…”
Section: Marked Correlation Functions and Marked Variogramsmentioning
confidence: 99%
“…In such situations, the study of size correlation and size autocorrelation in trees spatial distribution patterns can identify the underlying competition relationship of nearby trees [31,33,34,[37][38][39][40][41]. Strong competition interactions between neighbouring trees that cause size hierarchies (unequal-sized neighbouring) often leads to asymmetric competition, which was defined as larger-sized trees obtaining a disproportionate share of resources (for their relative size) and suppressing the growth of smaller ones [42,43]. If asymmetric competition occurs between a pair of trees at close proximity during forest development, the bigger-sized individual receives more resources for growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation